2018
DOI: 10.1002/jcp.26303
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of single‐cell RNA sequencing data from mouse spermatogonial and mesenchymal stem cells to identify differentially expressed genes and transcriptional regulators of germline cells

Abstract: Identifying effective internal factors for regulating germline commitment during development and for maintaining spermatogonial stem cells (SSCs) self-renewal is important to understand the molecular basis of spermatogenesis process, and to develop new protocols for the production of the germline cells from other cell sources. Therefore, this study was designed to investigate single-cell RNA-sequencing data for identification of differentially expressed genes (DEGs) in 12 mouse-derived single SSCs (mSSCs) in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 66 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Although basal transcription components such as TFIID are not widely studied in the context of reproduction, Sisakhtnezhad and Heshmati [38] found that Taf7l (with Dazl, Mael, etc.) was one of the 30 most significantly SSC-enriched genes in comparison to mesenchymal stem cells in PND7 mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although basal transcription components such as TFIID are not widely studied in the context of reproduction, Sisakhtnezhad and Heshmati [38] found that Taf7l (with Dazl, Mael, etc.) was one of the 30 most significantly SSC-enriched genes in comparison to mesenchymal stem cells in PND7 mice.…”
Section: Discussionmentioning
confidence: 99%
“…was one of the 30 most significantly SSC-enriched genes in comparison to mesenchymal stem cells in PND7 mice. In addition, Taf1, Taf2, Taf4b, Taf7, Taf7l2, and Taf9b were also significantly enriched in SSCs along with other basal transcription machinery such as RNA-PII subunits [38]. Soh et al found that Taf4b, Taf5, Taf7l, Taf7l2, and Taf9b were "ovarian germ cell enriched", of which Taf7l, Taf7l2, and Taf9b are also highlighted as "meiotic prophase" genes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics has the potential to identify genes differentially expressed in patients with osteoporosis, predict hub genes based on protein interactions and gene enrichment analyses, and identify the responsible molecular mechanisms [9,10]. Bioinformatics analysis has been widely used to identify disease mechanisms and search for target genes [11,12].…”
Section: Agingmentioning
confidence: 99%
“…In mammalian somatic cells, there are at least four different Cdks to regulate the interphase of mitosis: Cdk2, Cdk3, Cdk4, and Cdk6. After interphase, Cdk1 drive cells through mitosis (Figure 2A) [60,61]. To perform kinase activity, CDK must bind to a cyclin as a regulatory protein.…”
Section: Gene Regulation Of Mitosis During Mammalian Gametogenesismentioning
confidence: 99%